Relationship of vascular endothelial growth factor expression and microvessel density with clinicopathological features of triple-negative breast cancer - ZHAO Benxin>, WANG Fei, LIU Pei, HAN Rongbo (Zhongguo lin chuang yan jiu, 2024)
"Objective To detect the expression of vascular endothelial growth factor (VEGF) and microvessel density in cancer tissues of breast cancer patients, and to analyze their relationship with clinicopathological characteristics of breast cancer. Methods Ninety-six breast cancer patients treated at the Fourth Affiliated Hospital of Nanjing Medical University from December 2021 to December 2022 were selected as the research subjects. According to whether the pathology was confirmed as triple-negative breast cancer (TNBC), they were divided into the TNBC group (24 cases) and the non-TNBC group (72 cases). Immunohistochemistry was used to detect the expression of VEGF protein in breast cancer tissues, and microvessel density was evaluated by immunohistochemical labeling of endothelial cells followed by counting the number of microvessels. The relationship between the two and the clinicopathological characteristics of breast cancer was analyzed. Results The positive rate of VEGF in TNBC patients(66.67%) was higher than that in non-TNBC patients (25.00%), with a significant difference (χ2=13.662, P＜0.01); the microvessel density in TNBC patients（66.04±10.29) was higher than that in non-TNBC patients (61.07±10.36), with a significant difference (t=2.039, P=0.044). In the TNBC group, the positive expression rate of VEGF in patients with clinical stage Ⅰ-Ⅱ and no lymph node metastasis was significantly lower than that in patients with clinical stage Ⅲ and lymph node metastasis (P＜0.05), and the microvascular density in patients with tumor diameter≥2 cm and clinical stage Ⅲ was significantly higher than that in patients with tumor diameter＜2 cm and clinical stage Ⅰ-Ⅱ (P＜0.05). In non-TNBC group, there was no significant difference in VEGF positive expression rate and microvessel density between patients with different clinicopathological characteristics (P＞0.05). Conclusion In TNBC patients, the high expression of VEGF and the increase of microvessel density are related to the tumor diameter, clinical stage and lymph node metastasis of TNBC, which is helpful to predict the prognosis of patients and provide a new way to target VEGF pathway or microvessel therapy."